PROTOCOLO DE IDENTIFICAÇÃO E MANEJO DA DOR PARA RECÉM NASCIDOS EM UNIDADE DE TERAPIA INTENSIVA NEONATAL - Naujorks, Silvia (2022)
The lack of verbalization makes pain management for newborns (NBs) admitted to a neonatal intensive care unit (NICU) a challenge. In view of the large number of potentially painful procedures to which they are submitted, and that several studies have already demonstrated the deleterious effects of this exposure, tools have been developed to try to measure pain and allow its identification and management. Therefore, the training of professionals involved in the care of these patients is necessary in order to improve the quality of care provided to NBs. Scientific objective: To know how professionals who work in a NICU identify, analyze and manage pain in hospitalized NBs. Technological objective: To create a protocol for the identification and management of pain in newborns, using already validated tools in the NICU. Method: This is an action-research study, whose methodological course was conducted through the steps that guide this type of study, the research trigger being the absence of a protocol for pain management of NB in a NICU of a hospital in medium size in the interior of the State of Rio Grande do Sul (RS). After approval by the hospital institution and by the Ethics and Research Committee of the educational institution, a validated questionnaire was applied, with multiple choice questions about knowledge and practices of neonatal pain management, to physicians, nurses, nursing technicians and physiotherapists working in a neonatal intensive care unit in the Central Region of the State of RS. After analyzing the answers obtained and a review of the literature, the tools most compatible with the team's level of knowledge were selected and a care protocol proposal was built. This protocol prototype was initially sent for contributions from the medical and nursing leadership, and then it was presented to a group of team volunteers, for discussion and adjustments. After final formatting of the protocol, it was sent to the HUSM Quality Management System for analysis, validation by specialists and public consultation, with subsequent training of the team through recorded classes and made available via link, and face-to-face workshops. Through the Permanent Education Nucleus, it is intended to hold reviews and training on the subject every six months. Results: The data collected by the research instrument revealed an important gap in the team's knowledge regarding the importance of the topic of pain in the newborn, demonstrated through the inconsistent use of pharmacological and non-pharmacological measures in its prevention and management. Through the answers obtained, it was possible to select the most appropriate tools for use by the team and composition of the assistance protocol for the identification and management of neonatal pain. Product and Applicability: this is a care protocol that will impact the quality of care for NBs, and can be replicated in other neonatal units. Conclusion: Pain should not be neglected. After several studies demonstrating the ability of NBs, even extremely premature ones, to feel pain, combined with the deleterious effects caused by their prolonged exposure, it is necessary that this topic be prioritized within the line of neonatal care and the importance of developing care protocols.